HLA-C*01 is a Risk Factor for Crohn's Disease. Issue 4 (April 2016) - Jung, Eun Suk; Cheon, Jae Hee; Lee, Ji Hyun; Park, Soo Jung; Jang, Hui Won; Chung, Sook Hee; Park, Myoung Hee; Kim, Tai-Gyu; Oh, Heung-Bum; Yang, Suk-Kyun; Park, Sang Hyoung; Han, Jae Yong; et al.
Abstract : Background: A dysregulated mucosal immune response to the intestinal environment in a genetically susceptible host is hypothesized to be critical to the pathogenesis of Crohn's disease (CD). Therefore, we examined CD-susceptibility genes involved in the immune response through a genome-wide association study and consecutive genotyping of human leukocyte antigens ( HLA s) and killer cell immunoglobulin-like receptors. Methods: An initial genome-wide association study was performed with 275 CD patients and 2369 controls from a Korean population. To validate the loci identified in the genome-wide association study, replication genotyping was performed in a different cohort of 242 CD patients and 1066 controls. Finally, high-resolution genotyping of HLA and killer cell immunoglobulin-like receptor was performed. Results: Four susceptibility loci, a promoter region in tumor necrosis factor (ligand) superfamily member ( TNFSF15 ) and 3 independent regions in HLA s, showed significant associations with CD. Among them, rs114985235 in the intergenic region between HLA-B and HLA-C showed the strongest association, with an increased risk of CD ( P = 8.71 × 10 −23 ; odds ratio, 2.25). HLA typing in this region showed HLA-C*01 to be responsible for the association of CD among 43 HLA-B and HLA-C genotypes identified in the Korean population. However, the interaction of HLA-C with killer cell immunoglobulin-like receptor had little effect on the development of CD. Conclusions: We newly identified HLA-C*01 as a prominent CD-susceptibility HLA allotype in the Korean population. In addition, these results confirm that genetic variations in immune response genes, such as HLA s and TNFSF15, are important host factors for the pathogenesis of CD. Abstract : Supplemental Digital Content is Available in the Text.Article first published online 18 February 2016.